Experimental investigation of abrasive finishing with robotic application - Shankara Narayanan, Padmanabhan (2017)
This dissertation project is based on optimization of process parameters in the abrasive robotic finishing process. The effect of certain process parameters on the surface finish of the abraded surface is studied using the design of experiments (DOE) methodology and investigated experimentally. The DOE concepts are implemented on abrasive robotic finishing processes. The finishing or polishing operation is very vital in any manufacturing plant. Methods have evolved from hand finishing operations to automatic finishing using CNC machines presently. This research would pertain to the next level of finishing with the help of a robot. A set of influential parameters that are critical to a grinding operation is chosen as input parameters. The influence of the selected parameters on a specific output is to be analyzed and investigated. The material removal would be brought about with the help of abrasives in the form of cutting too ls. Coated abrasives like fiber disc s and non- woven type surface conditioning discs are chosen as the cutting tools. Minitab statistical software is used in planning the design and for optimizing the results. The optimized parameters are experimentally verified in an abrasive robotic finishing operation. A comparison between the two sets of too ls on the too l life/wear is do ne and a critical analysis on their performance is tabulated.